Crack mothers, crack babies, and black male dope dealers productions of deviance during america's crack cocaine panic in the 1980s - Yandow, Chantelle (2011)
A moral panic erupted during the 1980s among the American public when stories about crack cocaine saturated the media. In this thesis I analyze how discursive productions of deviancy operated in the CBS news documentary: 48 Hours on Crack Street (1986) and other print news sources at that time. Three salient characters that appear in news media discourse during the panic are crack mothers, crack babies, and Black male dope dealers. The news media frightened the public with such representations (among others) and the public urged politicians to get tough on drug crime to control the so-called crack cocaine plague. Politicians responded with omnibus drug reforms that established mandatory minimum sentences and the controversial 100:1 sentencing disparity between crack and powder cocaine. The enforcement of the draconian drug laws that were passed in response to the crack cocaine panic continues to be a contributing factor to America's current prison crisis. Moreover, the laws are enforced in ways that disproportionately punish the poor and African-Americans. I conclude that the criminal disenfranchisement of millions of people since the 1980s relates to the media's representation of the crack cocaine epidemic and the legislation that was passed to control illicit drugs such as crack cocaine